Synthesis of Substituted 1,2-Dihydroisoquinolines by Palladium-Catalyzed Cascade Cyclization–Coupling of Trisubstituted Allenamides with Arylboronic Acids - Masahiro Yoshida; Ryunosuke Imaji; Shinya Shiomi (Molecules, 2024)
1,2-Dihydroisoquinolines are important compounds due to their biological and medicinal activities, and numerous approaches to their synthesis have been reported. Recently, we reported a facile synthesis of trisubstituted allenamides via N-acetylation followed by DBU-promoted isomerization, where various substituted allenamides were conveniently synthesized from readily available propargylamines with high efficiency. In light of this research background, we focused on the utility of this methodology for the synthesis of substituted 1,2-dihydroisoquinolines. In this study, a palladium-catalyzed cascade cyclization–coupling of trisubstituted allenamides containing a bromoaryl moiety with arylboronic acids is described. When N-acetyl diphenyl-substituted trisubstituted allenamide and phenylboronic acid were treated with 10 mol% of Pd(OAc)2, 20 mol% of P(o-tolyl)3, and 5 equivalents of NaOH in dioxane/H2O (4/1) at 80 °C, the reaction proceeded to afford a substituted 1,2-dihydroisoquinoline. The reaction proceeded via intramolecular cyclization, followed by transmetallation with the arylboronic acid of the resulting allylpalladium intermediate. A variety of highly substituted 1,2-dihydroisoquinolines were concisely obtained using this methodology because the allenamides, as reaction substrates, were prepared from readily available propargylamines in one step.